The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph182010647
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impacts of COVID-19 on Healthcare Trainees and Perceptions towards a Digital Wellbeing Support Package

Abstract: We explore the impact of COVID–19 on the psychological wellbeing of healthcare trainees, and the perceived value of a digital support package to mitigate the psychological impacts of the pandemic (PoWerS Study). This mixed–methods study includes (i) exposure to a digital support package; (ii) participant survey to assess wellbeing, perceptions of work and intervention fidelity; (iii) semi–structured qualitative interviews. Interviews were digitally recorded and transcribed, data were handled and analysed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…We did not collect data on the type of degree that the students were registered for, and there may be differences in students' experiences during the pandemic. For example, prior research has suggested that students' willingness to discuss mental well-being (or other personal challenges), and the level of pastoral support they receive, can vary across disciplines [13]. Further, there may be differences in experiences of students registered on taught programmes, compared with those on research degree programmes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not collect data on the type of degree that the students were registered for, and there may be differences in students' experiences during the pandemic. For example, prior research has suggested that students' willingness to discuss mental well-being (or other personal challenges), and the level of pastoral support they receive, can vary across disciplines [13]. Further, there may be differences in experiences of students registered on taught programmes, compared with those on research degree programmes.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Studies are rapidly emerging which explore the psychological impacts of the COVID-19 pandemic on university students [4,10,11,13]. Students have faced considerable emotional challenges following COVID-19 restrictions, such as feelings of loneliness, stress, low mood, anxiety, and depression [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of the pandemic on university staff and students has been recognised [ 2 , 3 , 4 , 5 , 6 , 51 ]. Our participants indicated that the provision of testing onsite was beneficial, both for wellbeing and a perception of feeling safe on campus.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a major global public health burden, associated with high morbidity and mortality [ 1 ]. In a higher education context, the negative impacts of COVID-19 and social restrictions on students and faculty are well-documented [ 2 , 3 , 4 , 5 , 6 ]. On university and college campuses, virus transmission risk is high, associated with a social culture [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-care (alongside structural, organisational and job-related factors) is one aspect of health and well-being, that is strongly advocated in supportive interventions that have arisen during the COVID-19 pandemic. For example, a digital support package developed for health and care workers and trainees [117,118] emphasises the value of aspects of self-care such as diet, exercise, shift-work and sleep, all of which are known to be related to overweight and obesity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%